The Economics of Recognizing and Restoring Indigenous Property Rights to Water - Sanchez, Leslie. (Tufts University. Tisch Library., 2022)
Thesis (Ph.D.)--Tufts University, 2022.; Submitted to the Dept. of Agriculture, Food and Environment.; Advisor: Timothy Griffin.; Committee: Sean Cash, and Eric Edwards.; Keywords: Natural resource management, Economics, and Law.